If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying lnx + x = 5 Solving lnx + x = 5 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-1x' to each side of the equation. lnx + x + -1x = 5 + -1x Combine like terms: x + -1x = 0 lnx + 0 = 5 + -1x lnx = 5 + -1x Divide each side by 'nx'. l = 5n-1x-1 + -1n-1 Simplifying l = 5n-1x-1 + -1n-1 Reorder the terms: l = -1n-1 + 5n-1x-1
| 5x^2+6x+13=0 | | 9y-11=-10x+5 | | 7.6(4.5z-3)+3= | | y+8=7x | | ln(m)=.5(ln(x^2-y)) | | x/2-29=22 | | -5(-3)(-7)(-1)= | | 7(x+3)+2=7x+9 | | 3x^2/3x | | 0.18(2x)=29.5 | | 8x+10y=170 | | 0.18(2x)=59 | | y-15x=3 | | -17.3-m=22.8 | | 5+30=x+6 | | 2xy+10=90 | | x^9=-7 | | 3x+39=0 | | 3i*3i= | | -0.9(7.5w-6)-9= | | i*3i= | | 9(x-4)+x=10(x-4)+4 | | .02=15.4 | | -5x+3.6=2.1-4x | | 7.5(-0.9w-9)-6= | | x^2+2=3y | | 3x^3+5x-24=0 | | 4x+8x=2(6x-12) | | 4(8-5x)=25 | | -8+22=15x-2-14x | | (8a-5x)2= | | x-6=-2-24 |